PRELIMINARY PHYTOCHEMICAL ANALYSIS AND ANTIMICROBIAL POTENTIAL OF FERMENTED BAMBUSA BALCOOA SHOOTS - S. ANIL SINGH,; T. C. BORA,; N. RAJMUHON SINGH, (The Bioscan, 2012)
Preliminary phytochemical screening of solvent extracts viz. methanol and ethyl acetate of fermented Bambusa balcooa shoots were carried out. Study reveals the presence of tannins, steroids, phenols, glycosides, flavanoids, carbohydrates and proteins. FT-IR spectrum in the mid infrared region (4000-400cm-1) shows the presence of N-H, C=O, C-H, C=C and C-O, C-C, C-O bonds responsible for alkyl groups, methyl groups, alcohols, ethers, esters, ketones, carboxylic acid, anhydrides and deoxyribose confirming the qualitative results. Further, the therapeutic potential was confirmed by the antimicrobial property of the methanolic extracts against 4 bacterial strains viz., Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa and Escherichia coli and 3 fungal strains viz., Aspergillus niger, Candida albicans and Fusarium oxysporum. Maximum activity was observed against Staphylococcus aureus (18mm), Bacillus subtilis (15mm) followed by Pseudomonas aeruginosa (13mm) and Escherichia coli (11mm). While no activity was observed against Aspergillus niger and Candida albicans, significant activity was seen against Fusarium oxysporum (9mm).